2013
DOI: 10.3748/wjg.v19.i34.5607
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy andClostridium difficilecolitis: Relationships revealed by clinical observations and immunology

Abstract: Advances in understanding the interaction between the human immune system and the microbiome have led to an improved understanding of the function of the vermiform appendix as a safe-house for beneficial bacteria in the colon. These advances have been made despite long standing clinical observations that the appendectomy is a safe and effective procedure. However, more recent clinical data show that an appendectomy puts patients at increased risk for recurrent Clostridium difficile (C. difficile)-associated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…On the other hand, the dysbiosis of the intestinal microbiota in the cecum and large intestine was not observed, suggesting that the intestinal microbiota has been buffered in the passage of the cecum, because a branched cecum appendix is an apparent safe niche for intestinal bacteria. Thus, the appendix maintains the microbial biofilm composed of indigenous bacteria [32,33]. Considering these results, the microbiota recovery effect observed in the cecum is likely to be important to protect the large intestine from some undesirable bacteria.…”
Section: Compound Name Group (Ethanol/sn13t) a (−/−) B (+/−) C (−/+) mentioning
confidence: 97%
“…On the other hand, the dysbiosis of the intestinal microbiota in the cecum and large intestine was not observed, suggesting that the intestinal microbiota has been buffered in the passage of the cecum, because a branched cecum appendix is an apparent safe niche for intestinal bacteria. Thus, the appendix maintains the microbial biofilm composed of indigenous bacteria [32,33]. Considering these results, the microbiota recovery effect observed in the cecum is likely to be important to protect the large intestine from some undesirable bacteria.…”
Section: Compound Name Group (Ethanol/sn13t) a (−/−) B (+/−) C (−/+) mentioning
confidence: 97%
“…However, awareness is increasing regarding the importance of this seemingly insignificant organ in the development and preservation of gut-associated lymphoid tissue (GALT) and the interaction with intestinal fl ora ( 1,2 ). With the growing number of reports linking the appendix to both the prevention and development of various pathologies (e.g., Clostridium diffi cile and ulcerative colitis (UC)), a better understanding of its function and the role of the commensal gut fl ora on immunology might be helpful in daily clinical practice (3)(4)(5).…”
mentioning
confidence: 99%
“…19 Furthermore, many studies have suggested that appendectomy may increase the risk of ulcerative colitis, colon cancer, C. difficile colitis, and rheumatic arthritis. [6][7][8][9] In this large, retrospective, population-based cohort study, we revealed that the risks of CKD (aHR 1.13, 95% CI 1.01-1.26, P = 0.037) and ESRD (aHR 1.59, 95% CI 1.06-2.37, P = 0.024) were higher among appendectomy patients than in the control cohort. These results support our supposition that there are associations between appendectomy and CKD and ESRD.…”
Section: Discussionmentioning
confidence: 81%
“…5 The appendix also contains the highest concentration of gut-associated lymphoid tissue, which has numerous functions. 6 Appendectomy is expected to profoundly alter the immune system and modulate the pathogenic inflammatory immune responses of the gut. 6 Furthermore, studies have shown that appendectomy-related impairment of the microbiota may lead to dysbiosis and induce various diseases, including ulcerative colitis, Crohn's disease, Clostridium difficile infection, colorectal cancer, rheumatoid arthritis, and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation